ON-FARM ASSESSMENT OF TWO NUTRITIONAL STRATEGIES ON PRODUCTION EFFICIENCY AND NUTRIENT EXCRETION IN BROILER PRODUCTION IN NIGERIA - AKANDE, T. O.; OLATUNJI, A. O.; SALAKO, A. O.; ADEGOKE, A.; OLABIYI, O. M.; BALOGUN, B. M. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2023)
This study was carried out to assess the effect of two nutritional strategies on production efficiency and nutrient excretion in commercial broiler production in Nigeria. The study was carried out at Dovetech Farms Consult, Nigeria, in conjunction with Obafemi Awolowo University, Ile-Ife, Nigeria. Twelve thousand one-day-old Abor Acre broilers obtained in six batches of two thousand each were used for the study. Each batch was raised separately and in succession in the same house with an area of 280 m2. Experimental treatments were composed of two feed types. The first three batches were fed with conventional low-nutrient feed while the last three batches were raised on high-nutrient feed. Feed intake and body weight were monitored daily and weekly, respectively. Twenty birds from each batch were placed in the metabolic cages to determine nutrient digestibility and excretion of N, Ca and P. The Two-Sample T-test method was used to analyze the data. The two nutritional strategies supported the growth of broilers differently (p<0.05). Birds on high and low-nutrient feeds reached 1.9 kg body weight in 37 and 47 days, respectively. There was higher (p<0.05) daily feed intake, body weight gain, and better feed conversion in high-nutrient feed than low-nutrient feed. Broiler performance efficiency factor (BPEF) and Broiler farm economy index (BFEI) were both superior in high-nutrient feed while feed cost per kg weight gained did not differ (p>0.05) in both feeding strategies. Feed digestibility was better in high-nutrient feed but no significant difference (p>0.05) was observed in the excretion of all nutrients assessed. High-nutrient feed was more efficient and did not constitute any significant threat to the environment in terms of nutrient excretion over the conventional low-nutrient feed.